Students' Perception of the “Two-Stage” Collaborative Examination Based on the Focus Group Interview Method - Wang, Li Ming; Wang, Yan Chun; Li, Shan Shan; Jin, Ying (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Two-stage collaborative exams have been proven to improve students’ performance and enhance students’ learning efficiency. However, there is no quality study on students' perception of two-stage exams through Focus Group Discussion (FGD). Herein, the FGD method was implemented to explore students' perceptions of the two-stage exam. Materials and Methods: Third-year undergraduate pharmacy students participated in a two-stage exam with a natural product chemistry course. Students were required to complete the test individually and then answer the same questions again in small groups. Then, nine students comprising three high achievers, three middle achievers and three low achievers were recruited for the purposive sampling method of focus group discussion. Strengths, weaknesses and suggestions for implementing the two-stage exam were investigated. Data were transcribed and thematically analysed. Results: The interviewed students indicated that the two-stage exam gave them a chance to go over the answers of the exam while they still remembered the questions. They participated positively in the discussions and received immediate, specific feedback and then improved their mastery of knowledge. Conclusion: The two-stage exam as a remedy to the traditional exam was viewed favourably by students. The implementation of a two-stage examination can further enhance their learning experience and effectively improve learning efficiency.
Keywords: Collaborative Examination; Focus Group Interview; Immediate Feedback; Learning; Efficiency